RESEARCH OF VALUE OF DEFORMATION, STRESS AND SELF FREQUENCY OSCILLATION OF THE STAR SENSOR WITH EQUIVALENT INERTIAL WEIGHTING - R. V. Feodortsau; E. Y. Rogojinsky; K. V. Barkin; D. V. Cherenko (Приборы и методы измерений, 2015)
The 3D-model of the star sensor was design in the Pro/ENGINEER program. Mechanical analysis of rigidity of the construction was carry out in MSC Patran program. The value of the deformation and equivalent stress by gravitation 1g and 30g for loading by axis X, Y, was carry out. Account of self frequency in range of 200 to 6000 Hz was compute, and for the first 10 modes were received shapes of oscillation of the device.